Fluoride content of Los Angeles County water - Duperon, D F; Jedrychowski, J R; Kong, J (Journal of the California Dental Association, 1995)
A series of tap water samples were collected from residents in various areas of Los Angeles County. Three samples were collected each week over a period of three weeks, for a total of nine samples from each of the 45 residences. Samples were analyzed for fluoride content, and the data compared to information received from the agencies supplying the source water. Fluoride levels varied an average of .11 ppm during the three-week collection period; mean levels were consistently higher than values reported by the various agencies.